Structure–function relationships in the Nab2 polyadenosine‐RNA binding Zn finger protein family. (16th January 2019) - Fasken, Milo B.; Corbett, Anita H.; Stewart, Murray
Abstract: The poly(A) RNA binding Zn finger ribonucleoprotein Nab2 functions to control the length of 3′ poly(A) tails in Saccharomyces cerevisiae as well as contributing to the integration of the nuclear export of mature mRNA with preceding steps in the nuclear phase of the gene expression pathway. Nab2 is constructed from an N‐terminal PWI‐fold domain, followed by QQQP and RGG motifs and then seven CCCH Zn fingers. The nuclear pore‐associated proteins Gfd1 and Mlp1 bind to opposite sides of the Nab2 N‐terminal domain and function in the nuclear export of mRNA, whereas the Zn fingers, especially fingers 5–7, bind to A‐rich regions of mature transcripts and function to regulate poly(A) tail length as well as mRNA compaction prior to nuclear export. Nab2 Zn fingers 5–7 have a defined spatial arrangement, with fingers 5 and 7 arranged on one side of the cluster and finger 6 on the other side. This spatial arrangement facilitates the dimerization of Nab2 when bound to adenine‐rich RNAs and regulates both the termination of 3′ polyadenylation and transcript compaction. Nab2 also functions to coordinate steps in the nuclear phase of the gene expression pathway, such as splicing and polyadenylation, with the generation of mature mRNA and its nuclear export. Nab2 orthologues in higher Eukaryotes have similar domain structures and play roles associated with the regulation of splicing and polyadenylation. Importantly, mutations in the gene encoding the human Nab2 orthologue ZC3H14 and cause intellectual disability.